Experimental study of the development of centrifugal circulation in a liquid under various boundary conditions - Sharifullin Bulat; Naumov Igor (E3S Web of Conferences)
In this work, an experimental study was carried out on the formation of the structure of a limited vortex flow of a liquid swirled by a flow of another liquid or a gas vortex. The results obtained were compared with the structures that arise in closed vortex reactors, where the movement in the working volume is formed by a rotating disk. During the work, patterns of formation of circulating vortex cells in liquid were revealed. A similarity of the flow structure in the working fluid is observed, regardless of the method of creating the swirl (solid disk, liquid vortex, air vortex).